Perspectives on corpus linguistics - Viana, Vander; Zyngier, Sonia; Barnbrook, Geoff (Studies in corpus linguistics ;, 2011)
Perspectives on Corpus Linguistics is a collection of interviews with fourteen well-known researchers in the field of linguistics. Each interview consists of a set of ten questions: the first seven are common to all contributors while the last three are connected to the research experience of each guest. In the general questions, the invited scholars explore (sometimes controversial) topics such as the concept of representativeness, the role of intuition and the status of Corpus Linguistics. In the specific questions, they provide a thorough discussion of materials and methods in corpus.